2022
DOI: 10.1167/iovs.63.1.30
|View full text |Cite
|
Sign up to set email alerts
|

Hyperglycemia Induces Meibomian Gland Dysfunction

Abstract: Purpose Patients diagnosed with diabetes are inclined to have abnormalities on stability of tear film and disorder of meibomian gland (MG). This study aims to explore the pathological change of MG induced by diabetes in a rat model. Methods Sprague-Dawley (SD) rats were intraperitoneally injected with streptozotocin (STZ) to establish a diabetic animal model. Lipid accumulation in MG was detected by Oil Red O staining and LipidTox staining. Cell proliferation status was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
11
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(12 citation statements)
references
References 56 publications
1
11
0
Order By: Relevance
“… 1 , 35 We found that proinflammatory stress could facilitate lipogenesis and accelerate the terminal fate of HMGECs related to the overactivation of apoptosis and autophagy, which may play a pathologic role in lipid abnormalities and acini dropout in MGD. Consistent with our findings, Guo et al 10 recently reported that there was a prominent proinflammatory cytokine response, lipid accumulation, glandular dropout, and cell death in rats with MGD induced by hyperglycemia. Kim et al 54 also suggested that autophagy was initiated and mediated for cellular disintegration during the late differentiation of HMGECs.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“… 1 , 35 We found that proinflammatory stress could facilitate lipogenesis and accelerate the terminal fate of HMGECs related to the overactivation of apoptosis and autophagy, which may play a pathologic role in lipid abnormalities and acini dropout in MGD. Consistent with our findings, Guo et al 10 recently reported that there was a prominent proinflammatory cytokine response, lipid accumulation, glandular dropout, and cell death in rats with MGD induced by hyperglycemia. Kim et al 54 also suggested that autophagy was initiated and mediated for cellular disintegration during the late differentiation of HMGECs.…”
Section: Discussionsupporting
confidence: 93%
“… 9 In addition, prominent inflammatory cell infiltration and proinflammatory cytokine responses were detected in the MG microenvironment in a rodent MGD model induced by hyperlipidemia and hyperglycemia. 10 , 11 Abnormal accumulation of intraductal lipids from meibocytes and hyperkeratinization of MG ductal cells are important features of MGD. 8 , 12 Studies have reported that the pathology of ductal hyperkeratinization involves the overexpression of keratin 1 in MG ductal cells induced by proinflammatory stimulation.…”
mentioning
confidence: 99%
“…The LFU is essential in producing and maintaining a healthy tear film to help preserve ocular surface homeostasis. Previous studies have shown that diabetes produced altered morphology in the LFU structures, with decreased secretory granules in the lacrimal gland, decreased conjunctival goblet cell density, and decreased acinar size in Meibomian glands [ 25 27 ]. We found morphological alterations in the diabetic LFU after 6–7 weeks of hyperglycemia, with topical NTX altering only goblet cell deficits after 10 days of treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, the inflammatory microenvironment of the MG under diabetic conditions was indicated. It was also found that inflammatory cell infiltration apparently increases and inflammatory cytokine expression was significantly elevated in the MG of DM rats [ 31 ].…”
Section: Discussionmentioning
confidence: 99%